Selenium nanoparticles modified niobium MXene for non-enzymatic detection of glucose - Prabisha K. E.; Neena P. K.; Menon Ankitha; P. Abdul Rasheed; P. V. Suneesh; T. G. Satheesh Babu (Scientific Reports)
Abstract Glucose sensing remains a crucial need as diabetes is a worldwide concern. This work reports the application of Nb2CT x —selenium nanoparticle composite material for the nonenzymatic sensing of glucose. The surface morphology of the synthesized composite was analyzed using various microscopic techniques like scanning electron microscopy, transmission electron microscopy, and its structural properties were analyzed using diffraction and spectroscopic methods. A gold disc electrode was modified using the nanocomposite and tested for glucose in an alkaline medium. The sensing was based on the oxidation of glucose on the catalytic surface. The glucose was quantified amperometrically at a significantly lower overpotential of 0.16 V. The sensor showed a good detection range from 2 to 30 mM with a sensitivity of 4.15 µA mM−1 cm−2 and a detection limit of 1.1 mM.